1993
DOI: 10.1017/s037689290003719x
|View full text |Cite
|
Sign up to set email alerts
|

Park–People Relations in Kosi Tappu Wildlife Reserve, Nepal: A Socio-economic Analysis

Abstract: Park-people interactions in Kosi Tappu Wildlife Reserve, located in the lowlands of Southeastern Nepal, were studied intensively over a two-years' period from 1986 to 1988, through a variety of economic and attitu-dinal surveys. The Reserve had been established for the conservation of wild Water Buffalo and migratory waterfowl, and protects some of the most important wetland habitat in Nepal; it is therefore vital for the conservation of biodiversity on a national and regional level. The results showed that pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
121
2
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 11 publications
13
121
2
2
Order By: Relevance
“…Further positive change may be attributed to the greater opportunity to gain benefits from the reserve through non-agricultural employment among educated persons since they are less likely to be living at the margin of subsistence. These findings concur with those at Kossi Tappu wildlife reserve in Nepal, where respondents with higher household literacy rates had positive attitudes towards the reserve (Heinen 1993). They are also similar to findings by Akama et al (1995), they reported as the level of education increases, the level of negativity towards the reserve decreases.…”
Section: Demographic and Socio-economic Profile Of Respondentssupporting
confidence: 87%
“…Further positive change may be attributed to the greater opportunity to gain benefits from the reserve through non-agricultural employment among educated persons since they are less likely to be living at the margin of subsistence. These findings concur with those at Kossi Tappu wildlife reserve in Nepal, where respondents with higher household literacy rates had positive attitudes towards the reserve (Heinen 1993). They are also similar to findings by Akama et al (1995), they reported as the level of education increases, the level of negativity towards the reserve decreases.…”
Section: Demographic and Socio-economic Profile Of Respondentssupporting
confidence: 87%
“…Similarly, illegal livestock grazing inside the park and transaction of forest products causes this imbalanced relationship (Studsord & Wegg 1995, Tamang & Baral 2008, Shrestha 1994. Among all these issues, damage to crops, livestock, property and also human life because of wildlife interferences have been regarded as one of the severe problems faced by protected areas worldwide (Heinen 1993, Nyhus et al 2000, Perez & Pacheco 2006, Rao et al 2002, Weladji & Tchamba 2003. Park-people conflicts due to wildlife interference in the livelihood of communities often jeopardize the relationship between local communities and the protected area itself.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial economic losses, due to crop damage by wildlife, have been reported in many studies (Parry and Campbell, 1992;Newmark et al, 1993;Heinen, 1993;Studsrod and Wegge, 1995;Udaya-Sekhar, 1998; Naughton-Traves, 1998; Rao et al, 2002). Similarly, the wild boar could have heavily affected the local economy in many areas about 20 to 30 years ago in Turkey (Eroğlu and Baskaya, 1995).…”
Section: Resultsmentioning
confidence: 99%